Establishment of a Biolistic-Mediated Transformation System for an Indigenous Fragrant Orchid, Phalaenopsis Violacea - Chew, Yee Chern (2006)
Phalaenopsis, orchid recognised by its moth-like shape, orderly arranged flower, and long flower shelf-life, is one of the most important orchids grown for commercial production of cut flowers and potted plants. A study was carried out to develop the genetic transformation system for an indigenous fragrant orchid species - Phalaenopsis violacea Witte as this system is important for the development of novel orchid varieties with improved floriculture features and marketability. Protocorm-like bodies (PLBs) were successfully induced from leaf segments of in vitro seedlings, culturing on ½ strength Murashige and Skoog (MS) medium containing auxin 2,4-D (0.2, 0.4, 0.6, 0.8 and 1.0 μM) and NAA (0.4 and 0.6 μM) in three months. The highest frequency of PLBs formation was scored at 53 % on ½ strength MS basal medium containing 0.8 μM 2,4-D. However, using ½ MS medium supplemented with each 0.4 and 0.6 μM auxin. NAA to induce PLBs, the frequency of PLBs induction was lower than 15 %. No PLBs induction observed when auxin picloram and dicamba were employed to leaf segments at a series of concentration examined (0.2, 0.4, 0.6, 0.8 and 1.0 μM). Among all the organic additives [banana homogenate (BN), tomato homogenate (TM), coconut water (CW) and taro homogenate (TR)] tested in various concentrations (range 10, 20, 30, and 40 % w/v or v/v) for PLBs multiplication, optimal proliferation of PLBs was achieved through culturing on ½ MS medium supplemented with 10 % w/v BN. However, all the organic additives examined were found stimulated to PLBs growth in the concentration range of 5-10 % w/v or v/v compared to control treatment. Plant regeneration of PLBs was achieved in PGR-free ½ MS basal medium (with or without 10% w/v BN). The effectiveness of hygromycin in selecting transformed tissues has been investigated based on the minimal hygromycin level that capable to thoroughly inhibit and/or killed all the non-transformed tissues. Phalaenopsis violacea Witte PLBs had shown a high sensitive respond to hygromycin as a low concentration (4 mg/L) of hygromycin was sufficient to meet the requirements. Potential physical and biological parameters affecting DNA delivery into Phalaenopsis violacea Witte PLBs have been optimised. Green fluorescence protein (GFP) was served as the reporter system except in the study of ‘Influence of co-bombardment plasmid DNA ratios on transient expression’, both GFP and β-glucuronidase (GUS) detection were employed. Based on the optimised results, the ideal bombardment conditions were as followed: 6 cm target tissues distance, 1100 psi acceleration pressure, 1.0 μm gold particle size, 27 mmHg chamber vacuum pressure, 1 X bombardment time, spermidine for DNA coating on gold particle, 72 hours post-bombardment incubation time, 2 μg of total plasmid amount and 2:1 as the ratio of plasmid DNA used. Two putative transformed lines (recovered from hygromycin selection) were achieved from a total of 160 PLBs bombarded using the optimised transformation parameters, thus, 1.25 % transformation efficiency was obtained. However, the post-cultivation period after bombardment was found to be critical as the putative transformed PLBs were only produced with 30 post-cultivation days (indirect hygromycin selection), while selection without going through post-cultivation after bombardment (direct hygromycin selection) failed to produce any putative transformant. Pattern and behaviour of GFP expression along the path to regeneration were observed on line A putative transformant PLBs that recovered from hygromycin selection after 6-11 months of culture. Young cells or tissues showed strong green fluorescence while matured tissues gradually faded and lost their green fluorescence. Polymerase chain reaction (PCR) results that referred to the presence of transgenes (gfp, gusA, and hptII) in line A putative transformant PLBs (including second and third generation clonal progenies) showed that 100 % over the 32 samples tested were positive. All the gfp, gusA and hptII genes were retained from first to second and to third generation of clonal progenies in the putative transformants. However, no p35S::chs transgene was detected in both putative transformants lines as believes incorporated DNA might be fragmented during or after the bombardment events. Subsequently, accomplishment in DNA sequencing double confirmed the presence of gfp, gusA and hptII transgenes in the putative transformed PLBs.